Re-imagining the kitchen as a site of memory. (18th May 2016) - Meah, Angela; Jackson, Peter
Abstract: Extending the focus of previous geographical research on public spaces of remembering, this paper demonstrates the ways in which memory work also takes place in private domestic spaces. The paper draws on a combination of life history and ethnographic research undertaken in Northern England, examining kitchens as a specific lieu de mémoire, showing how they serve as places where valued items are displayed and material artefacts are curated as part of the construction and reproduction of personal memories and familial identities. Using ethnographic and visual evidence from two case study households, the paper demonstrates the role of material artefacts in curating the past and materialising memory. Additionally, life history interviews with older women reveal narratives of everyday cooking practices which seemingly contradict popular discourses of the past, questioning conventional ideas about the distorted nature of nostalgia. In combination, our data represent complex narratives in which the past can be seen as infusing the present, and where present-day concerns are revealed as actively shaping public discourses which favour a return to an idealised past, which may have little bearing on people's actual lived experience.